POTENTIALS OF THE CAT’S WHISKER PLANTS (Orthosiphon aristatus) FOR KIDNEY HEALTH - Yudith Yunia Kusmala; Nasywa Fathiyya A; Naura Khanza M. Z; Alia Fatimah M; Soraya Riyanti (Fakultas Kedokteran Gigi Unjani, 2023)
The cat's whisker plant (Orthosiphon stamineus) can be useful as an antioxidant, anti-inflammatory, antihypertensive, antidiabetic, and anti-microbial activity and has a diuretic effect. The leaves of the cat's whiskers are medicinal plants that contain flavonoid compounds. Cat whiskers plant can also be used to treat various types of diseases both empirically and clinically, including kidney stones. Kidney stones are a clinical disorder due to the blockage of the components of crystal stones that inhibit the work of the kidneys and can cause abnormalities in the urinary tract. Some constituent compounds that are usually found in kidney stones are calcium oxalate, calcium phosphate (brusit), uric acid, cystine, struvite (MgNH4PO4), and wedelit (Bakta, 1995). Efforts to treat kidney stones by utilizing a variety of herbs as medicine, in this context by using a cat whiskers plant called Alternative Medicine, this is because herbal plants have minimal side effects in long-term use when used with the right indications and proportions, the price is also more affordable and easy to obtain. The purpose of this paper is to discuss and provide information on morphology, secondary metabolite content, and pharmacological activity of cat whiskers plants so that they can be used as a support for kidney health. This research is a study of literature or literature review is a type of research that collects, manages, uses, and reviews research data sourced from scientific research journals, previous research manuscripts, and textbooks that have relevance to the theme. The results of a literature search indicate that the cat's whisker plant can be beneficial for kidney health because the extract has diuretic activity and can modulate the excretion of sodium and potassium ions in the urine. The presence of flavonoids, saponins, and phenolic compounds that play a role in diuresis activity, so this cat whiskers plant is efficacious in treating kidney stone disease because it has the effect of destroying kidney stones, reducing urine (diuretic) and anti-inflammatory (anti-inflammatory). DOI : 10.54052/jhds.v2n3.p387-404